A review of economic factors influencing voluntary carbon disclosure in the property sector of developing economies - Kalu, J. U. (Institute of Physics Publishing, 2016)
Global warming has consequences on the environment and economy; this led to the establishment of United Nation Framework Convention on Climate Change (UNFCCC) and the Kyoto Protocol. These two agreements were to reduce greenhouse gases (GHG) emissions which are responsible for climate change and global warming. Developing countries under the protocol are not obligated to reduce or disclosure GHG emission, so their participation in the protocol is on voluntary mitigation bases. This study intends to examine economic factors that influence voluntary carbon disclosure in the property sub-sector of developing countries based on annual report of listed property companies in Malaysia. Signaling theory addresses the problem of information asymmetry in the society. Disclosure is an effective tool to overcome information imbalance among different market participants. The study hypothesizes that the economic factors that influence voluntary carbon information disclosure in developing countries are: [1] the company's size; this is because a large-sized company have more resources to cover the cost of reducing pollution. [2] The company's gearing status; where there is no sufficient information disclosure in a highly geared company will result to an increased agency cost. [3] Profitability; profits grants companies a pool of resources for mitigation activities and environmental reporting. Also, carbon disclosure acts as a means for achieving public confidence and legitimacy. [4] Liquidity: Companies that are highly liquid will disclosure more information to distinguish themselves from other companies that are less liquidity. This is correlated to environmental disclosure. [5] Financial slack affects companies' ability to participate in green technology projects that enable a reduction in emission.